Aplicação prolongada de gel dessensibilizante antes e após o clareamento dental em consultório para evitar a sensibilidade induzida pelo clareamento: ensaio clínico, randomizado, triplo-cego - Silva Júnior, Wilson da (2019)
Some studies showed the use of potassium nitrate/sodium fluoride desensitizing agents might reduce the intensity of tooth sensitivity (TS). This trial evaluated the use prolonged of 5% potassium nitrate/0.2% sodium fluoride desensitizing agents ten days before and after in-office bleaching to avoid the TS. A parallel, placebo-controlled, triple-blind, randomized trial, was conducted on 115 healthy adults having teeth shade A2 or darker. The patients used 5% potassium nitrate/0,2% sodium fluoride desensitizing agents or placebo gel, for 10 days in a tray for 10 min, prior, during and two days after to the in-office bleaching (35% hydrogen peroxide). The primary outcome TS was recorded on VAS 0-10 and NRS 0-4 scales, during bleaching and in periods that ranged from 1-6 h, 12-18 h, 18-24 h and 24-48 h post-bleaching. The color was measured before and one month after dental bleaching with two visual shade guides (Vita Classical and Vita Bleachedguide) and Easyshade spectrophotometer. The primary outcome variable was absolute risk of TS. An intent-to-treat analysis was used to analyze data from all patients who were randomly assigned to receive the desensitizing and placebo gel. No significant difference (p = 0.66) in the absolute risk of TS between the desensitizing group (80%; 95% CI 69 to 89) and placebo group (88%; 95% CI 77 to 94) with a relative risk of 1.1; 95% CI 0.9 to 1.3. No significant differences between groups were observed in terms of intensity of TS and color change (p > 0.05) for any of scales. No adverse effect was observed. The use of 5% potassium nitrate/0,2% sodium fluoride desensitizing agents 10 days before and after in-office bleaching does not reduce the risk and intensity of bleaching-induced TS